Evaluasi Pola Hubungan Tentara Nasional Indonesia dan Kepolisian Republik Indonesia dalam Pertahanan dan Keamanan Negara: Evaluation of the Relationship Pattern Between the Indonesian National Armed Forces and the Republic of Indonesia Police in National Defense and Security - Mochamad Insnaeni Ramdhan; Muhamad Ikhwan Pratama; Ananda Sorya Pratama Desmala (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
The Indonesian National Armed Forces and the Indonesian National Police are state institutions that serve to maintain national defense and security. However, when carrying out their respective duties, they often overlap and are inconsistent in their roles and functions. This study evaluates the pattern of relations between the two institutions in order to strengthen national defense and security through constitutional provisions. The research method used is a normative-prescriptive approach with a qualitative methodology to identify the pattern of relations between the two institutions based on the laws governing them. The conclusion drawn from this study is that the relationship pattern formed based on the laws governing the two institutions is a coordinative relationship because both institutions are under the President. However, as long as the President assigns them, the Indonesian National Armed Forces can also support police authority. This leads to overlapping roles that raise questions about the security and defense aspects. According to this study, the National Legal Development Board's (BPHN) Guideline for Evaluation of Legislation No. PHN-HN.01.03-07 regulatory substances are coherent. As a result, it is necessary to maintain consistency in the concepts of security and defense as well as the constitutionally mandated division of institutional roles.